ANALISIS KELAYAKAN FINANSIAL SISTEM PENGELOLAAN SAMPAH DI DESA PENEBEL KABUPATEN TABANAN - DEWA AYU PUTU ADHIYA GARINI PUTRI; ADIE WAHYUDI OKTAVIA GAMA (GANEC SWARA, 2020)
Waste is currently a major issue in the development of the current tourism paradigm towards sustainable tourism. Waste management is certainly needed to keep the environment clean and beautiful. Waste management does not only reach urban areas, but also includes rural areas. One of them is in the area of Penebel Village, Penebel District, Tabanan Regency. Penebel Village is currently conducting an independent waste management effort at the village level. The Penebel Village area currently consists of 9 banjar dinas which have a total population of 4,175 people. One effort has been made is to design a 3R Integrated Waste Management Site (TPST) within the Penebel Village. The study conducted is a financial feasibility analysis of the waste management system found in Penebel Village. Based on the results of a financial feasibility study on the waste management model in Penebel Village, the NPV value is Rp. 694,166,994,426, -> 0 and the value of BCR is 2.58> 1. Both NPV and BCR values are greater than the specified conditions, so the investment is declared NPV> 0 and BCR> 1.